Autonomous water and nutritional anti‐stress device to solve a plant irrigation problem based on harvested rainwater: A Tunisian case study. (19th February 2021) - Medhioub, Samir; Euchi, Jalel; Makhloufi, Slim
Abstract: Water consumption has increased significantly around the world in recent years, whereas existing water resources are becoming rarer. Even in tropical areas, where the rains offer an average of 2600 mm of water yearly, the soil water source can reduce gradually throughout the dry season and limit the growth of vegetation. Different irrigation methods have been developed to meet plants' water needs for productivity. These methods depend closely on mobilization of the water source and its permanent control. In this paper, we have proposed an autonomous water and nutritional anti‐stress device for plants based on the recovery of rainwater. It is a new concept inspired by irrigation in antique clay pots. It is designed to ensure regular cyclical storage and transfer to the plant of an almost constant daily flow of mobilized rainwater. These waters are also enriched with nutrients during their journey to the plant. This delayed water storage and transfer process will compensate for the lack of water necessary for the survival of the plant in dry periods. The device was tested in a reduced environment and has given good results in decreasing water stress and increasing the level of nutrition for plants. Résumé: La consommation d'eau a considérablement augmenté dans le monde ces dernières années, alors que les ressources en eau existantes se raréfient. Même dans les zones tropicales, où les pluies offrent un volume moyen de 2600 mm d'eau par an, la source d'eau du sol peut diminuer progressivement tout au long de la saison sèche et limiter la croissance de la végétation. Différentes méthodes d'irrigation ont été développées pour répondre aux besoins en eau de la plante pour la productivité. Ces méthodes dépendent étroitement de la mobilisation de la source d'eau et de son contrôle permanent. Dans cet article, nous avons proposé un dispositif autonome anti‐stress hydrique et nutritionnel pour les plantes basé sur la récupération des eaux de pluie. C'est un nouveau concept inspiré de l'irrigation dans des pots en terre cuite antiques. Il est conçu pour assurer un stockage cyclique régulier et le transfert vers la plante d'un débit quotidien quasi constant d'eau de pluie mobilisée. Ces eaux sont également enrichies de nutriments lors de leur voyage vers la plante. Ce processus retardé de stockage et de transfert de l'eau compensera le manque d'eau nécessaire à la survie de la plante en période de sécheresse. L'appareil est testé dans un environnement réduit et il a donné un bon résultat pour diminuer le stress hydrique et augmenter le niveau de nutrition des plantes.